2017
DOI: 10.1155/2017/1583098
|View full text |Cite
|
Sign up to set email alerts
|

Cinnamon Polyphenol Extract Inhibits Hyperlipidemia and Inflammation by Modulation of Transcription Factors in High‐Fat Diet‐Fed Rats

Abstract: We evaluated the effects of cinnamon polyphenol extract on hepatic transcription factors expressions including SREBP-1c and LXR-α in rats fed high fat diet (HFD). Twenty-eight Wistar rats were allocated into four groups: (i) normal control: animals fed with normal chow; (ii) cinnamon: animals supplemented with cinnamon polyphenol; (iii) HFD: animals fed a high-fat diet; and (iv) HFD + cinnamon: animals fed a high-fat diet and treated with cinnamon polyphenol. Obesity was linked to hyperglycemia, hyperlipidemia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
86
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(93 citation statements)
references
References 55 publications
6
86
0
1
Order By: Relevance
“…Cinnamaldehyde has been predicted to have an anti-oxidative function along with a protein modulatory function as outlined by our underlying hypothesis (Tulini et al 2016;Tuzcu et al 2017). Fig.…”
Section: Discussionmentioning
confidence: 94%
“…Cinnamaldehyde has been predicted to have an anti-oxidative function along with a protein modulatory function as outlined by our underlying hypothesis (Tulini et al 2016;Tuzcu et al 2017). Fig.…”
Section: Discussionmentioning
confidence: 94%
“…A large number of studies have reported the beneficial effects of dietary flavonoids on human health (Hossain et al, 2016). Numerous flavonoids including those in Paulownia fortunei flowers, green tea, and cinnamon have been found to protect against obesity-related complications, such as type 2 diabetes mellitus, cardiovascular disease, and nonalcoholic fatty liver disease (Liu et al, 2017;Tuzcu, Orhan, Sahin, Juturu, & Sahin, 2017;Yamashita et al, 2018). However, to our knowledge, there is no report on anti-obesity activity of prenylated flavonoids in the seeds of P. corylifolia L. We found that PFE protected against obesity and significantly reduced bodyweight, fat mass, and white adipose cells in the HFD-induced obese mice.…”
Section: Discussionmentioning
confidence: 99%
“…( Figure 4C), and to the MDA content, in a dose-dependent manner ( Figure 4E). It has been demonstrated that plant polyphenols are related to the improvement of hepatic oxidative stress caused by a high-fat diet through the e activation of Nrf2 transcription factor, which increases expression of antioxidant enzymes [37]. Moreover, it was reported that even the single polyphenol, if isolated, can improve the high-fat-diet-induced hepatic oxidative stress, as in the case of rutin [33] and gallic acid [38].…”
Section: The Effect Of Psf On Liver and Brain Oxidative Stress Of Ratsmentioning
confidence: 99%